INFLUENCE OF SERVICE QUALITY, PRICE AND LOCATION ON CUSTOMER SATISFACTION AT AHASS 05468 WORKSHOP SETYA MOTOR SURABAYA (HONDA DEAD C ) - Kunto Inggit Gunawan; Ec. Mataji (Jurnal Scientia, 2023)
This research is a study conducted at the AHASS 05468 Setya Motor Surabaya workshop with the title "The Influence of Service Quality, Price , and Location on Customer Satisfaction at AHASS 05468 Setya Motor Surabaya Workshop Services".This study proves that: (1) From the results of the F Test (Simultaneous Test) a value of 0.000 <0.05 is obtained, which means that the variables of Service Quality, Price , and Location have a simultaneous significant influence on customer satisfaction in choosing AHASS 05468 Setya Motor workshop services Surabaya. (2) From the results of the t-test (Partial Test) for X1 found 0.000 <0.05, X2 = 0.007 <0.05 and X3 = 0.004 <0.05 meaning that the three variables have a partially significant effect on customer satisfaction in choosing AHASS services workshop 05468 Setya Motor Surabaya. (3) The results of the Multiple Linear Regression Analysis found Y=0.219+0.532X1+0.232X2+0.297X3 indicating that the service quality variable has a value of b1=0.532, and this indicates that the largest value means that it has the most dominant influence. (4) The results of the Multiple Correlation Coefficient Analysis R have a value of R=0.828, meaning that the x and y variables simultaneously have a very strong relationship. (5) The results of the Coefficient of Determination R2 have a value of R-square = 0.685 meaning that 68.5% of the customer satisfaction variable is explained by the variables perceived service quality, price , and location , while the remaining 31.5% is influenced by other variables not included in the study.